(3QLhY GdTjN dUHGIs - (3CMeO Hf jhSa GdJjaGTj, TgGH GdOjf CHh GdYHGS,J (B651 (3g` s
(3ChdgG (B:s
(3GdMeO ddg dGPj Ndb GdGTjGA HbOQJg Effj deG QGjJ GdTghGJ cdgG efhWI HCSHGH GdHGg hOGYjI Zdi GdLeGY Hd LeYJg ef GdcJH GdeUfaI aj GdjGg s
(3BNQgG (B:s
(3CNQj hRjf OGfb HRQHfM heKdg Cajhf eUQj hJe LejY GdcJGH HYhf Gdedd GdhgGH s
(3hajg cJGHI HNW JYdjb bde eNJda hbO fSjJ aj fSN CNQj dGHf ceGd HGTGs
(3hgh NWCs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs